Development of Interactive Learning Media Mobile Learning In Science for Class VIII Junior High School - Jodi Hardika; Ridwan Ridwan; Alwen Bentri; Ramalis Hakim; Rayendra Rayendra; Fetri Yeni J (Postgraduate, University of Mataram, 2024)
This research focuses on the development of interactive mobile learning media for science subjects in eighth-grade junior high school. The identified problems are the lack of student engagement and the limitations of easily damaged learning media. Additionally, educators face difficulties in using technology in the teaching and learning process. This study uses the research and development (R&D) method with a 4-D model. The product's validity was assessed by six experts—two media experts, two language experts, and two subject matter experts—who rated it as